Vibration response analysis of PZT-4/PZT-5H based functionally graded tapered plate subjected to electro-mechanical loading. (September 2021) - Kumar, Pawan; Harsha, S.P.
Highlights: Detailed vibrational study of the FGP plate with tapered thickness is presented. A modified power law estimates both effective electrical and mechanical properties. Finite element formulation (6 DOFs per node) is used. Convergence & parametric studies are carried out, show the efficacy of this method. Different tapered ratios and electric potential effects are studies. Abstract: In this paper, the vibration responses of the tapered functionally graded piezoelectric (FGP) square plate are analyzed. The governing equations are obtained using the first-order shear deformation theory (FSDT) with the variational (Hamilton's) principle, and the solution is obtained using nine-noded isoperimetric elements based finite element method. The effective electrical and mechanical properties are varying power-law distribution along the thickness direction. The tapered FGP plate is composed of PZT-4 (Top-side) and PZT-5H (bottom-side). Convergence and comparison tests have been carried out to validate the exactness of the current method. The numerical results are presented to analyze the effect of side to thickness( a / h )ratio, tapered ratio(ℏ), power law exponent( N ), applied electric voltage( V )and the different boundary conditions for the tapered FGP square plate. The results show that the FGP tapered plate frequencies are influenced by the tapered ratio, volume fraction exponent, side to thickness ratio, and the applied electric voltage. These findings can be used to design smart structures based on the functionally graded piezoelectric material.